The Dark Side of Migration Remittances and Development: The Case of Edo Sex Trade in Europe - Odorige, Catherine Enoredia (Pécs journal of international and European law, 2016)
Migrants’ remittances outflow to developing nations has gained wide attention in recent times. This is due to the fact that it has surpassed the amount in total aid money from developed nations to these developing nations. According to World Bank estimates in 2011 remittances by migrants in the United Kingdom to India is 4billion USD compared to 450million USD aid to the country in that same year1. When looked at in real terms it means how much impact these money can have on the developmental strides of developing countries in the long and short run. The remittance flow to developing nations in 2008 was put at 336 billion US dollars and in 2009 it was 316 billion US dollars from developed countries.2 These remittances have in no small way had increased positive impact on the ways of life of persons and relatives living in these less developed countries. It is a relief to many homes from the grip of intense poverty. But the question is how much of these remittances are from legitimate and morally right sources? This paper seeks to look at remittances from Europe to Edo state of the federal republic of Nigeria and analyse the possible sources of remittances that have had an impact on the lives of the peoples of Edo state.